Manifesting evil: Demons and physical monstrosity in the Testaments of the Twelve Patriarchs. (December 2019) - de Bruin, Tom
The interplay between spiritual evil and physical monstrosity plays a large role in the Testaments of the Twelve Patriarchs . The Testaments are structured around the understanding of a human spirit, the mind, which stands between good and evil spirits, and in general it is the mind that forms the focus of the text's exhortation. The evil spirits influence the mind, causing a person to think unrighteous thoughts and ultimately commit unrighteous acts. The role of the mind, however, is so large that it even plays a dominant role in the physical appearance of a person. In this article, I examine three distinct cases where someone's ethical and spiritual evil results in physical monstrosity. First, we see that when someone's mind follows the temptations of an evil spirit, they become disabled. Second, we see that an evil spirit has the power to poison someone's own neutral spirit, which ultimately leads the poisoned person to manifest themselves in a monstrous way. Finally, women bear monstrous giants as a direct result of their mental lust for the angelic Watchers. These three cases show the close relationship between external appearance and internal demeanor in the Testaments . Thus, humankind functions as a means through which the invisible monstrous manifests itself in the visible world. This realization helps clarify some early Christian understandings of humankind's natural and monstrous states, as well as their ideas about ethics and social conduct, the nature of evil, and how the manifestation of evil in the physical world is influenced.